Electoral incentives when the stakes are low: a case study from an economics department - Francesco De Sinopoli; Giovanna Iannantuoni; Diego Lubian (Public Choice, 2026)
Abstract Since the pioneering work of Lizzeri and Persico (2001), it has been well known that, in winner-take-all systems, office-motivated politicians may favor targeted redistribution over the provision of public goods. Motivated by the possibility that similar incentives may arise even in small organizations, we examine a policy proposal to revise a journal-ranking system in a medium-sized Economics Department. At the same time, a majority of faculty members signed a petition on an unrelated issue publicly supporting the department’s governance. Using individual publication records, we analyze whether the distributional consequences of the proposed reform were systematically related to such support. We find that faculty members who signed the petition were significantly more likely to benefit from the initial proposal, while this association became considerably weaker after an open departmental discussion and a subsequent revision of the proposal. The observed pattern is consistent with theories emphasizing distributive incentives and the disciplining role of transparency in collective decision-making though alternative readings of the revision cannot be excluded.